Hubungan antara Kompensasi dan Sikap Proaktif dengan Motivasi Kerja Karyawan pada Industri Perhotelan - Morissan Morissan (Jurnal Manajemen dan Kewirausahaan, 2018)
Motivation of employees will be a determining factor for the success of the company, especially in in the hotel industry, where contact between employees and customers is relatively intensive. The quality of work will decrease if employees unsatisfied and it can be felt directly by guests. One of important variables that can affect working motivation is compensation. Good compensation will encourage employees to work well and more productive. Working motivation is also closely related to proactive behavior. This study aims to determine the relationship between employees perceptions of compensation and proactive behavior to working motivation. The respondents are 700 employees working in 37 stars and non-star hotels throughout Indonesia. The result shows that there is a relationship between employees perceptions of compensation and proactive behavior to working motivation.   https://doi.org/10.26905/jmdk.v6i2.2362